Geology and Wine 14. Terroir of Historic Wollersheim Winery, Lake Wisconsin American Viticultural Area - Karakis, Snejana; Cameron, Barry; Kean, William (Geoscience Canada, 2016)
The viticultural history of Wisconsin started in the 1840s, with the very first vine plantings by Hungarian Agoston Haraszthy on the Wollersheim Winery property located in the Lake Wisconsin American Viticultural Area (AVA). This study examines the terroir of historic Wollersheim Winery, the only winery within the confines of the Lake Wisconsin AVA, to understand the interplay of environmental factors influencing the character and quality as well as the variability of Wollersheim wines. Soil texture, chemistry, and mineralogy in conjunction with precision viticulture tools such as electromagnetic induction and electrical resistivity tomography surveys, are utilized in the Wollersheim Winery terroir characterization and observation of spatially variable terroir at the vineyard scale. Establishing and comparing areas of variability at the plot level for two specific vineyard plots (Domaine Reserve and Lot 19) at Wollersheim Winery provides insight into the effects of soil properties and land characteristics on grape and wine production using precision viticulture tools. The viticultural future of Wisconsin looks quite favourable, as the number of wineries keeps rising to meet the demand for Wisconsin wine and local consumption. As climate change continues to affect the grape varieties cultivated across the world’s wine regions, more opportunities arise for Wisconsin to cultivate cool-climate European varieties, in addition to the American and French-American hybrid varieties currently dominating grape production in this glacially influenced wine region.